The Possibilities and Social Impact of Using Open-Source Technologies in Education - Karshiyevna, Muminova Umida (Journal of Innovation in Education and Social Research, 2025)
This article discusses in detail the nature of open source technologies, their role in education, the opportunities they create, and the positive impact they have on society. The article shows students how open technologies are transforming the educational process and creating equal opportunities.